Seasonal migrations of the Yellow Wagtail Motacilla flava (Aves, Passeriformes) according to results of the trapping and ringing data for sixty-four years in the Eastern Baltic - Payevsky, Vladimir A.; Shapoval, Anatoly P. (Acta Biologica Sibirica, 2023)
Based on the results of trapping and ringing Yellow Wagtail on the Courish (Curonian) Spit in Eastern Baltic in the amount of 3076 individuals during 1957–2020, the population numbers, the migration routes and wintering grounds are presented. The obtained seven recoveries of our rings account for only 0.23% of the efficiency of Yellow Wagtail ringing. The annual number of Yellow Wagtails captured varied widely over 64 years, from three to 206 individuals. The oscillations were wavelike in nature and showed different amplitudes. Of the seven birds with our rings found two birds in November and February were caught in the Federal Republic of Nigeria (West Africa), three birds during migration were found in Italy and two birds during the summer were found in Sweden and Finland. The length of the migration route from the Courish Spit to Nigeria was more than five thousand kilometers. The results of studying the migrations of this species in other countries and regions are discussed.